Parsing Syntaxis on Language Acquisition of 3-4-Year-Old Children of Playgroup Darussalam Banyuwangi - Nurin Nauvalia; Hairus Salikin (Pusat Pelatihan, Riset, dan Pembelajaran Bahasa, 2022)
The language acquisition of each child is different. Some children are perfect and good at language, but other children still have difficulties in language. This causes the other person also have difficulty understanding what they are saying. The purpose of this study was to determine the acquisition of language in children aged 3-4 years and to know the Parsing Syntax of the language of children aged 3-4 years in the Darussalam Study Group Blokagung Banyuwangi. The research design used is descriptive qualitative. Data were collected by applying observation and interviews with the teacher and the students of Playgroup of Darussalam. The data were analyzed using the Interactive model of Miles, Huberman, and Saldana. The results showed that language acquisition was obtained from the family environment, social environment, and school environment. The students of the Darussalam Blokagung Banyuwangi Playgroup have basic language acquisition. They tend to imitate or learn from the surrounding environment, family, school, or social environments.